Post Pandemic Public Acceptance Map Toward Ijen Geopark Using Aspect Based Sentiment Analysis Technique - Bagus Setya Rintyarna (Universitas Muhammadiyah Jember, 2022)
Tourism is one of the sectors that has been seriously hit by the impact of the Covid-19 pandemic indicated by the sharp decrease in the number of both domestic and foreign tourists visit. The decrease has also been experienced by the popular tourist destination located in the border of Bondowoso and Banyuwangi Regency namely Ijen Geopark. Since the tourism sector has shown a significant role as a driver of economic activity, the aim of this work is to build public acceptance map toward Ijen Geopark as the government reduce the limitation of the prohibition policy to handle the spread of Covid-19. Sentiment analysis is adopted to build the public acceptance map by using TripAdvisor dataset. To gain a fine grained, results we extent the technique using our proposed aspect-based sentiment analysis making use cosine similarity algorithm and several keywords. Using several keywords and cosine similarity algorithm, we succesfully extract aspect of the topic. Employing Naïve Bayes, we then labeled the sentiment orientation of the associated aspect extracted from sentence. During 2022, we highlight the fact that most tourist positively accept Ijen Geopark. Some parts that need to be evaluated by the decision maker and related party is Sulfur Mining and the cost since both aspect received more negative comment compared to the positive ones.